A program for ligation at threonine sites: application to the controlled total synthesis of glycopeptides - Chen, Jin (2010)
A method by which to accomplish formal threonine ligation has been developed. The method accomplishes ligations of two peptide domains. We have also demonstrated the ability to successfully ligate two independent glycopeptide domains.